A dielectric resonator bandpass filter using printed circuit board technology for wideband application. Issue 11 (1st September 2022) - Shi, Jin; Wang, Mengdan; Xu, Kai
Abstract: A dual‐mode dielectric resonator based on printed circuit board (PCB) technology formed bandpass filter is proposed for relatively wide bandwidth under low quality factor. By using the low dielectric constant substrate itself to become the core part of the two coupled dual‐mode resonators through the PCB process, the proposed design can share the same substrate with other PCB circuits and reduce the installation error. Moreover, benefiting from the dual‐mode ( TE 111 y mode and TM 111 z mode) resonator realized by low dielectric constant substrate with low quality factor, the proposed design exhibits the features of low cost and wide bandwidth. A prototype with the center frequency ( f 0 ) of 13.85 GHz was demonstrated, which shows the 3‐dB fractional bandwidth of 8.34% and the minimum insertion loss of 1.29 dB.